Análise ético-teológica de alguns mitos ribeirinhos do baixo Tapajós na defesa do meio ambiente - Costa, Ivair da Silva (2010)
In this study, Theological Ethics detains itself to the analysis of Amazon s reality and its problems, perceiving the disharmony and the forms of threats to nature, and offers answers from concrete practices of the riverside cultural system. In this cultural system, shaped by the corpus mithorum, by folklore, by the way of life, by the means of relating to nature and by the forms of utilization of the means of resources for subsistence, is found strength for the preservation of nature, whose defensive potential is analyzed in the light of Theological Ethics. The first chapter pursues a historical description of the occupation of the Amazon, since the first intervention by the European conqueror and the process of assimilation by which the population went through and is going through. The second chapter is preoccupied in describing and analyzing the Amazon mythology, perceiving its role in the lives of the population, their way of manifestation and their configuration in the life of the riverside population, recognizing the potential for defense of the environment present in it. The third chapter deepens the ethical-theological reflection of the cultural manifestations of daily life motivated by myths, perceiving the ethical attitudes present there and the forms of defense of the environment suggested in them. The present study adds to the current theological, ecological and ethical debate, offering theoretical bases for the promotion of alternatives for the harmony between nature and man, development with preservation, sustainability and conservation of the natural, social and cultural heritage, aiming at perspectives with which man assumes the alliance made with God and with creation, proclaiming the promotion of justice and solidarity as indispensable ethical values